Analogy of Law in Tax Law Regulation of Economic Relations Based on the Supply Chain Management - Alekseevich Mikryukov, Viktor (International Journal of Supply Chain Management, 2019)
The relevance is due to the variability and incompleteness of modern tax legislation, which results in increased attention to the problems of applying tax rules with the use of analogy as a key technique for overcoming legal lacunae. The objective is to enhance the development of the doctrinal frameworks for the practice of applying the analogy of law and to identify the peculiarities of the implementation of this tool in the area of tax. The methodological framework involves general scientific (analysis and synthesis, abstraction and concretization) and special research methods (comparative legal, formal legal, technical legal, teleological). The method of analogy is both the key tool and the object of study. Arguments are presented supporting the suitability of the method of analogy for use in tax law. The application of tax legislation by analogy has been substantiated to not only permissible, but also necessary for the proper protection of taxpayers’ rights and counteracting infringement of fiscal interests. The necessity of introducing measures of deterrence of law enforcer’s discretion when using the analogy in the impact of tax law is revealed. The arguments against the direct regulatory legalization of the analogy in the tax law are presented. The work contributes to the enhancement of the general doctrinal provisions on the application of the analogy of law and serves as the basis for creating special parameters for applying this tool in taxation.